A Guidebook for Assessing Mathematical Logic Intelligence in Kindergarten - Indah Abdiana; Nenny Mahyuddin (LPPM Undiksha, 2024)
Many children still need help understanding numbers; children also cannot differentiate between round, triangular, and square shapes. Apart from that, teachers only carry out assessments at the end of the learning semester and do not use assessment guides, especially on aspects of children's mathematical logic intelligence in their daily activities at school. Based on this, this research aims to develop a guidebook for assessing mathematical logic intelligence in kindergarten. This type of research is development research. This research uses the ADDIE model. The research subjects are learning media experts and learning material experts. The test subjects were fifteen teachers. The methods used to collect data are interviews, documentation, and questionnaires. The data collection instrument uses a questionnaire sheet. The data analysis technique used is quantitative descriptive statistical analysis. The research results are the results of material media validation tests with a test percentage value of 96.3% and the eligibility criteria being